Role of magnetohydrodynamic activity in sawtooth induced heat pulse propagation in ADITYA tokamak. (1st March 2023) - Patel, S.; Ghosh, J.; Chowdhuri, M. B.; Mayya, K. B. K.; Manchanda, R.; Pandya, H. K. B.; Tanna, R. L.; Kumar, V.; Joisa, S.; Purohit, S.; Raju, D.; Jha, S.; et al.
Abstract: Fast propagation of sawtooth induced heat pulse is observed in the magnetohydrodynamic (MHD) active plasmas of ADITYA tokamak. The sawtooth crash deposits heat beyond the inversion radius, which gets transported to the edge region of the plasma, and is reflected as inverted sawtooth modulation in the edge channels of electron cyclotron emission (ECE) and H α spectral line emission. The time-lag analysis on ECE signal reveals the propagation time from plasma core to edge of ∼150 µ s. From this analysis, the estimated transient electron heat diffusivity χ e hp is found to be ∼50–60 m 2 s −1, which is ten times higher than that of power balance heat diffusivity χ e pb, in the MHD active discharges of ADITYA. It has been observed that the presence of MHD ( m / n = 2/1, 3/1) activity in the intermediate region between the q = 1 and the edge radii, significantly influences the heat transport from the plasma core to the edge region. Stochastic magnetic field region formation with overlapping m / n = 2/1 and 3/1 MHD islands facilitates the fast heat-pulse propagation during a sawtooth crash in ADITYA tokamak. The disparity between the measured and the power-balance estimated diffusivity is significantly reduced by considering the electron heat diffusivity due to stochastization of magnetic field in the intermediate region.